Effects of Water Deficit at Tasseling on Photosynthesis, Development, and Yield of Corn - Nawarat Udomprasert; Janjaree Kijjanon; Katharat Chusri-iam; Aneknan Machuay (Agriculture and Natural Resources, 2005)
This study was conducted to determine the effects of water deficits on net assimilation rates and development which were causes of grain yield reduction in maize. Two maize inbreds, Ki3 (purported drought sensitive) and Ki11 (purported drought tolerance), were pot-grown in greenhouse. Plants were exposed to water deficit by withholding water until wilting occurred at tassel initiation and at anthesis. Water deficit at both stages reduced net assimilation rates (NAR) and relative growth rates (RGR) significantly in both maize inbreds. The reduction was more evident in Ki3 than that in Ki11. Water deficit at tassel initiation increased anthesis-to-silking interval (ASI) for 3 and 2 days in Ki3 and Ki11, respectively, while water deficit at anthesis increased ASI for only 1.25 and 0.75 days in Ki3 and Ki11, respectively. Considering yield and yield components, it was found that water deficits reduced ear girth, seed weight, grain yield, and harvest index in both inbreds. Water deficit at tassel initiation showed greater effects on those components than did the one at anthesis.